2008
DOI: 10.1093/cercor/bhn038
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Dynamics Subserving Visual Apparent Motion

Abstract: Motion can be perceived when static images are successively presented with a spatial shift. This type of motion is an illusion and is termed apparent motion (AM). Here we show, with a voltage sensitive dye applied to the visual cortex of the ferret, that presentation of a sequence of stationary, short duration, stimuli which are perceived to produce AM are, initially, mapped in areas 17 and 18 as separate stationary representations. But time locked to the offset of the 1st stimulus, a sequence of signals are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 65 publications
(104 reference statements)
3
90
0
Order By: Relevance
“…Feedback from higher-level visual areas to V1 seems a likely explanation for the effects of stimulus predictability reported here as these areas have larger receptive fields than V1, allowing them to determine the trajectory of long-range apparent motion (Angelucci and Bullier, 2003, Angelucci and Bressloff, 2006, Ichida et al, 2007. This fact, taken together with the observation that during long-range apparent motion hMT/V5ϩ sends feedback signals to V1 (Muckli et al, 2005;Sterzer et al, 2006;Ahmed et al, 2008;Wibral et al, 2008), can be considered a strong indication that activation in hMT/ V5ϩ drives the predictability effect in V1. However, several studies have suggested that local processing of feedforward signals in V1 allows for more sophisticated neural computations than one would expect from classical receptive field models (Seriès et al, 2002(Seriès et al, , 2003Masland and Martin, 2007).…”
Section: Discussionmentioning
confidence: 52%
“…Feedback from higher-level visual areas to V1 seems a likely explanation for the effects of stimulus predictability reported here as these areas have larger receptive fields than V1, allowing them to determine the trajectory of long-range apparent motion (Angelucci and Bullier, 2003, Angelucci and Bressloff, 2006, Ichida et al, 2007. This fact, taken together with the observation that during long-range apparent motion hMT/V5ϩ sends feedback signals to V1 (Muckli et al, 2005;Sterzer et al, 2006;Ahmed et al, 2008;Wibral et al, 2008), can be considered a strong indication that activation in hMT/ V5ϩ drives the predictability effect in V1. However, several studies have suggested that local processing of feedforward signals in V1 allows for more sophisticated neural computations than one would expect from classical receptive field models (Seriès et al, 2002(Seriès et al, , 2003Masland and Martin, 2007).…”
Section: Discussionmentioning
confidence: 52%
“…These brain regions are activated differentially, depending upon the given task at hand and the specific type(s) of cognition necessary to address it [60][61][62]. The prefrontal cortex is activated by all tasks, which likely reflects its primary role in the organization of thought.…”
Section: Expertise Giftedness Prodigy Intelligence-definitionsmentioning
confidence: 99%
“…This does not seem to be the case, as sub-threshold dV m (t)/dt increases very well may influence the subsequent dynamics of a neuron population both in single cortical neurons and at the mesoscopic neuron network scale. Indeed such dV m (t)/dt increases can be induced by neurons in other cortical areas Ahmed et al, 2008;Harvey et al, 2009;Niell and Stryker, 2010;Roland, 2010;Harvey and Roland, 2013;Zagha et al, 2013).…”
Section: Background and Scopementioning
confidence: 99%
“…Part of the explanation might be that the dye signal in vivo reflects synaptic activity at the mesoscopic scale, whereas the action potential recordings capture the activity of single neurons (Lippert et al, 2007;Eriksson et al, 2008). Nevertheless, in several studies one can follow how net increases in the synaptic activity propagate over the cortical areas when the cortex is perturbed by a sensory transient (Senseman, 1996;Prechtl et al, 1997;Senseman and Robbins, 2002;Slovin et al, 2002;Grinvald and Hildseheim, 2004;Roland et al, 2006;Ferezou et al, 2007;Lippert et al, 2007;Xu et al, 2007;Ahmed et al, 2008;Han et al, 2008;Takagaki et al, 2008;Yoshida et al, 2008;Harvey et al, 2009;Ayzenshtat et al, 2010;Meirovithz et al, 2010;Ng et al, 2010;Polack and Contreras, 2012;Harvey and Roland, 2013). This synaptic dynamics may show some order in the feed-forward propagation of net-excitation for example between V1 and V2 in monkeys, rats and turtles, between the barrel field and the motor cortex in the mouse, and between visual areas 17, 18 and 19, 21 in the ferret.…”
Section: Frontiers In Systemsmentioning
confidence: 99%
See 1 more Smart Citation